2022
DOI: 10.3390/molecules27113369
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Method for Quality Evaluation of Gardeniae fructus Praeparatus during Heat Processing Based on Sensory Characteristics and Chemical Compositions

Abstract: The intrinsic chemical components and sensory characteristics of Gardeniae fructus Praeparatus (GFP) directly reflect its quality and subsequently, affect its clinical curative effect. However, there is little research on the correlation between the appearance traits and chemical compositions of GFP during heat processing. In this study, the major components of five typical processed decoction pieces of GFP were determined. With the deepening of processing, the contents of geniposidic acid and 5-HMF gradually … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“… Xu et al (2015) compared the raw betel nut with its processed products of stir-frying yellow, stir-frying coke and stir-frying charcoal, and found that the contents of 5-HMF and arecoline in the three processed products were significantly different and closely related to the levels obtained by electronic nose and electronic tongue. Zheng et al (2022) used cluster analysis and Artificial neural network analysis (ANN) to better identify gardenia with various processing degrees. For the determination of the end point of processing, the color difference and distribution in the image may be used to determine the degree of stir-frying and cooking of the drug, so that the processing system may determine whether to use partial tumbling, or to end the processing when the decoction pieces reach the optimal efficacy; such processing system may avoid improper or excessive processing ( Lin et al, 2021 ).…”
Section: Applications Of Digital and Intelligent Technologies In Proc...mentioning
confidence: 99%
“… Xu et al (2015) compared the raw betel nut with its processed products of stir-frying yellow, stir-frying coke and stir-frying charcoal, and found that the contents of 5-HMF and arecoline in the three processed products were significantly different and closely related to the levels obtained by electronic nose and electronic tongue. Zheng et al (2022) used cluster analysis and Artificial neural network analysis (ANN) to better identify gardenia with various processing degrees. For the determination of the end point of processing, the color difference and distribution in the image may be used to determine the degree of stir-frying and cooking of the drug, so that the processing system may determine whether to use partial tumbling, or to end the processing when the decoction pieces reach the optimal efficacy; such processing system may avoid improper or excessive processing ( Lin et al, 2021 ).…”
Section: Applications Of Digital and Intelligent Technologies In Proc...mentioning
confidence: 99%